EPISTEMOLOGI PENYEMBUHAN TRADISIONAL: MUNGKINKAH UNTUK BERKOLABORASI DENGAN PENGOBATAN MODERN? - Hariati, Rima (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
Traditional healing is a popular alternative treatment chosen by many people. In contrast to modern medical treatment which is based on ratios, methodology, and scientific evidence, traditional healing has its own knowledge system. This research aim to explain the epistemology of traditional healing and explore the potential and challenges of integrating traditional healing with modern medicine. The research methodology involved a traditional literature review, including selecting a review topic, searching for related literature in the Google Scholar database, collecting and analyzing relevant literature, writing a review, and creating a bibliography. The results of this literature review explain the sources of traditional healing knowledge, how traditional healing knowledge is transmitted, and the potential and challenges of collaborating traditional healing with modern medical treatment. This research can be input for further studies on addressing the challenges and potential of collaboration between traditional healing and modern medical treatment, especially in Indonesia.